Pembinaan Sustainable Millennial Integrated Farming System Berbasis Kearifan Lokal pada Masyarakat di Desa Pesisir, Kecamatan Sumberasih, Kabupaten Probolinggo - Adi Sutrisno; Indra Tjahyadi; Hosnol Wafa; Sri Andayani; Sugeng Edy Mulyono; Nuril Hidayati; Rasyidah Nur Aisyah; Mohammad Zamroni (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
This community service aims to introduce the community in Pesisir Village, Sumberasih District, Probolinggo Regency regarding the Sustainable Millennial Integrated Farming System based on local wisdom through community development activities. The urgency of carrying out this activity is so that the people of Pesisir Village, Sumberasih District, Probolinggo Regency can increase sales of their agricultural products by utilizing a comprehensive and sustainable agricultural management system. This community service activity was carried out for six months in Pesisir Village, Sumberasih District, Probolinggo Regency. The method used in this activity is an offline mentoring and tutorial method in Pesisir Village, Sumberasih District, Probolinggo Regency. The highlight of this community service activity is the formation of a comprehensive agricultural management system that is familiar to the Pesisir Village community, and the implementation of a comprehensive, sustainable agricultural management system as an agricultural system in the Pesisir Village community, Sumberasih District, Probolinggo Regency.